The hot deformation behavior and 3D processing maps of 25Cr2Ni4MoV steel for a super-large nuclear-power rotor. (November 2020) - Ye, Liyan; Zhai, Yuewen; Zhou, Leyu; Wang, Huizhen; Jiang, Peng
Abstract: According to the characteristics of open die forging for heavy forgings, the compression tests in the temperature range of 1373−1523 K and strain rate range of 0.001−0.1 s −1 were finished for investigating the hot deformation behavior of 25Cr2Ni4MoV steel for a super-large nuclear-power rotor. The deformation activation energy was calculated about 356.79 KJ/ mol. The 3D processing maps were established based on dynamic materials model to reveal the hot workability. According to the processing maps, when the strain is less than 0.5, the processing map were strongly influenced by the temperature, strain rate and strain. At the strain of 0.9, the processing map was divided into four regions for researching the microstructure evolution. Defects such as mixed grain and large grain were observed at relatively high or low strain rates. 25Cr2Ni4MoV steel is not suitable to be processed at temperatures exceeding 1473 K. The optimum hot working domain was the area of 1378−1423 K/0.0067 s -1 -0.01 s -1 with a peak power dissipation efficiency of about 0.5.